South Africa and Covid-19 Pandemic: Unpacking the Strategies of Management and Control - Moshood, Abdul-Wasi Babatunde; Durokifa, Anuoluwapo (International Review of Management and Marketing, 2023)
South Africa at 6th September, 2021 recorded 2,824,063 cases of people with corona virus and 83,617 deaths resulting from COVID 19. It made over 1700 arrest to enforce strict compliance to the lockdown imposed on the country when the case started and has increased stimulus packages for companies and individuals to cushion the effect of lockdown on the economy. It has also increased the capacity for testing and has since eased the lockdown initially imposed on the country. Away from few cases of African countries such as Botswana and Tanzania, South Africa has adopted a methodology for managing COVID 19 pandemic that seems to be a direct adaptation from the advanced countries of the United States, France and the United Kingdom. This study using qualitative and participant observation methods investigates the process of managing the pandemic in South Africa, the extent to that has helped to flatten the curve of the spread and the impact it has on the people and the economy of South Africa generally. It probes further to query if there are homegrown alternatives that may be best suited to containing and managing situations of this nature going forward.